2021
DOI: 10.1111/jfpe.13823
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pretreatments on drying of red dacca in a single slope solar dryer

Abstract: Pretreatment of fruits normally increases moisture loss and reduces the overall drying period. The combination of pretreatments and drying assures the least color difference, excellent preservation, and better antioxidant activity. Pretreatment of Red Dacca is soaked in four different solutions, namely honey, lemon juice, sugar syrup, and ascorbic acid, for 10 min. The best solution for pretreatment is investigated

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 49 publications
(38 reference statements)
1
7
0
Order By: Relevance
“…The average solar radiation and ambient temperature were recorded as 794.18 W/m 2 and 34.33°C, with the maximum solar radiation and atmospheric temperature being 1002.03 W/m 2 and 36.75°C at 11 a.m., respectively. A similar trend was observed by Gatea, 44 Elavarasan et al, 45,46 Elavarasan and sendhil 47 …”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…The average solar radiation and ambient temperature were recorded as 794.18 W/m 2 and 34.33°C, with the maximum solar radiation and atmospheric temperature being 1002.03 W/m 2 and 36.75°C at 11 a.m., respectively. A similar trend was observed by Gatea, 44 Elavarasan et al, 45,46 Elavarasan and sendhil 47 …”
Section: Resultssupporting
confidence: 84%
“…[40][41][42][43] From, Figure 3 44 Elavarasan et al, 45,46 Elavarasan and sendhil. 47 From Table 2, it is observed that the Ash content is highest for forced convection drying (6.21 g/100 gm), followed by natural con-…”
Section: Resultsmentioning
confidence: 97%
“…Advances in Materials Science and Engineering (2) Te amount of water content (W) removed [21][22][23][24] (3) Instantaneous moisture content Mt is calculated for time 't'…”
Section: Energy and Exergy Analysismentioning
confidence: 99%
“…The drying process is playing an important role in heatsensitive product dehydration. Solar drying is a better choice to reduce the loss and produce good quality red dacca after harvesting (Elangovan and Natarajan, 2021). The dehydrated fruits are high in a range of dietary fibers and other bioactive compounds with prebiotic effects (e.g.…”
Section: Introductionmentioning
confidence: 99%